The Former Miss Barstow with every Tom, Dick and Harry in a doll’s house - Newton, Richard (Nordlit, 2015)
Julie Holledge, panel chairperson and member of the International Ibsen Committee, invited myself along with 3 others to participate in the Inaugural Artists’ Keynote Panel: Applied Ibsen on Four Continents: The Artists’ Intentions. My presentation focused on “The Former Miss Barstow with every Tom, Dick and Harry in a doll’s house.” This was an adaptation of Ibsen’s “A Doll’s House” produced and staged in Los Angeles, California, 1987. For the XIIIth International Ibsen Conference at the University of Tromsø, Norway, I projected images; a few found on the internet, and many from the production itself, as well as a video clip shown streaming live from YouTube. The article describes the social context of the 80s, analyzes the reinterpretation of Ibsen’s characters, and sets out to explain the symbology of the sets and costumes. I also touch on the differences between this production and Ibsen’s original in four important aspects. These would be the macaroons, the Tarantella, the silk stockings and the end of the play. Finally, I explain my decision to upload this version of “A Doll’s House,’ scene by scene, to my page on YouTube. Having shown films and videos for many years at festivals around the globe, I was looking for a way to step outside that box and reach an international audience just beyond my keyboard. In all of these ways, the goal has been to illuminate the ways in which an artist takes Ibsen’s text and applies it to the specific social context of their time and culture.